Lifestyle as Medicine: The Case for a True Health Initiative. Issue 6 (July 2018) - Katz, David L.; Frates, Elizabeth P.; Bonnet, Jonathan P.; Gupta, Sanjay K.; Vartiainen, Erkki; Carmona, Richard H.
The power of lifestyle as medicine was perceived thousands of years ago. There is now consistent and compelling science to support the important influence of lifestyle on health. Approximately 80% of chronic disease and premature death could be prevented by not smoking, being physically active, and adhering to a healthful dietary pattern. Cardiovascular disease, diabetes, stroke, dementia, and cancer are all influenced by lifestyle choices. Despite the ample evidence about what behaviors promote health, confusion still prevails among the general population. This is particularly true with regard to diet. Confusing nutrition messages from scientists, the media, the food industry, and other sources have made it all but impossible for any single authority to convey persuasively the fundamentals of healthful eating. The case is made here that a global coalition of diverse experts has the power to do what no individual can: clarify and popularize an understanding of the fundamentals of a health-promoting, sustainable pattern of diet and lifestyle, and rally the general public to their consistent support.